TAM kinase inhibition and immune checkpoint blockade– a winning combination in cancer treatment?. (1st February 2021) - Msaouel, Pavlos; Genovese, Giannicola; Gao, Jianjun; Sen, Suvajit; Tannir, Nizar M.
ABSTRACT: Introduction : Immune checkpoint inhibitors (ICI) have shown great promise in a wide spectrum of malignancies. However, responses are not always durable, and this mode of treatment is only effective in a subset of patients. As such, there exists an unmet need for novel approaches to bolster ICI efficacy. Areas covered : We review the role of the Tyro3, Axl, and Mer (TAM) receptor tyrosine kinases in promoting tumor-induced immune suppression and discuss the benefits that may be derived from combining ICI with TAM kinase-targeted tyrosine kinase inhibitors. We searched the MEDLINE Public Library of Medicine (PubMed) and EMBASE databases and referred to ClinicalTrials.gov for relevant ongoing studies. Expert opinion : Targeting of TAM kinases may improve the efficacy of immune checkpoint blockade. However, it remains to be determined whether this effect will be better achieved by the selective targeting of each TAM receptor, depending on the context, or by multi-receptor TAM inhibitors. Triple inhibition of all TAM receptors is more likely to be associated with an increased risk for adverse events. Clinical trial designs should use high-resolution clinical endpoints and proper control arms to determine the synergistic effects of combining TAM inhibition with immune checkpoint blockade.